2022
DOI: 10.1053/j.jvca.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Chest CT Severity Score Predicts Failure of Noninvasive Positive-Pressure Ventilation in Patients Hospitalized for COVID-19 Pneumonia

Abstract: Objective Non-invasive positive pressure ventilation (NPPV) emerged as an efficient tool for treatment of Coronavirus disease-19 (COVID-19) pneumonia. The factors influencing NPPV failure are still elusive. The aim of the study was to investigate the relationships between semiquantitative chest computed tomography (CT) scoring and NPPV failure and mortality in patients with COVID-19 Design Observational study Setting Non-intensive setting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Two studies [ 21 , 22 ] were conducted in Italy. Six studies [ 19 , 23 , 24 , 25 , 26 , 27 ] were conducted in India. Furthermore, two studies [ 18 , 28 ] were carried out in Pakistan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies [ 21 , 22 ] were conducted in Italy. Six studies [ 19 , 23 , 24 , 25 , 26 , 27 ] were conducted in India. Furthermore, two studies [ 18 , 28 ] were carried out in Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed a significant association between the CT severity score and clinical outcomes. Studies [ 22 , 23 , 24 , 25 , 26 , 28 , 33 , 34 , 38 , 40 , 41 , 42 ], found that the CT severity score is positively associated with mortality and morbidity rates (increased risk of mortality and morbidity), the need for mechanical ventilation and for emergency medical treatment, patient survival, inflammatory markers, endotracheal intubation, oxygen saturation and demand, respiratory rate, length of hospital stays (prolonged hospitalization, >21 days), increased risk of noninvasive positive-pressure ventilation (NIPPV) failure, ICU admission, vaccination status, age, gender, co-morbidities, and stage of disease in the cohort of COVID-19 patients. It has also been found that CT severity score is higher in patients with severe COVID-19 pneumonia compared to those with mild or moderate disease.…”
Section: Resultsmentioning
confidence: 99%
“…We are glad to provide answers to the stimulating comments made by Mungmunpuntipantipa and Wiwanitkit 1 to our article recently published in the Journal 2 . Regarding concomitant drug therapy, antibiotics, steroids, remdesivir and tocilizumab prescription rates in our population have been recently reported 3 . Hydroxychloroquine was used for a short period of time during the first wave only (March–April 2020).…”
Section: To the Editormentioning
confidence: 93%
“…2 Regarding concomitant drug therapy, antibiotics, steroids, remdesivir and tocilizumab prescription rates in our population have been recently reported. 3 Hydroxychloroquine was used for a short period of time during the first wave only (March-April 2020). Pertaining to the population of the present study, 2 we reanalyzed prescription rates of the aforementioned drugs according to the presence of underlying cardiovascular disease as well as cardiac biomarkers status and outcome, albeit finding no significant difference between groups.…”
Section: To the Editormentioning
confidence: 99%
“…While several studies have attempted to develop a prediction model for the need of MV or ICU admission, there is no well-accepted method that captures rapidly changing respiratory status in patients with COVID-19 [ 7 12 ]. Although some clinical scoring systems showed promising results with high discrimination, most use daily clinical data or those on admission and only predict deterioration within 24–48 h or thereafter [ 8 , 9 , 11 , 12 ]. Since candidates for MV are usually on oxygen therapy and changes in respiratory status are frequently assessed within a day, estimation with such a long-term interval using a score is not practical.…”
Section: Introductionmentioning
confidence: 99%